2004
DOI: 10.5194/angeo-22-2943-2004
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of resonant Alfvén waves generated by artificial HF heating of the auroral ionosphere

Abstract: Abstract. Numerical two-dimensional two-fluid MHD simulations of dynamic magnetosphere-ionosphere (MI) coupling have been performed to model the effects imposed on the auroral ionosphere by a powerful HF radio wave transmitter. The simulations demonstrate that modifications of the ionospheric plasma temperature and recombination due to artificial heating may trigger the ionospheric feedback instability when the coupled MI system is close to the state of marginal stability. The linear dispersion analysis of MI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
(31 reference statements)
1
12
0
Order By: Relevance
“…Generation of ULF waves by the ionospheric feedback instability at HAARP latitudes (near L = 4.9 dipole magnetic shell) can be modeled with reduced two‐fluid MHD (RMHD) equations [e.g., Pokhotelov et al , 2004]. The model consists of the parallel component of the electron momentum equation, the density continuity equation, and the current continuity equation.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Generation of ULF waves by the ionospheric feedback instability at HAARP latitudes (near L = 4.9 dipole magnetic shell) can be modeled with reduced two‐fluid MHD (RMHD) equations [e.g., Pokhotelov et al , 2004]. The model consists of the parallel component of the electron momentum equation, the density continuity equation, and the current continuity equation.…”
Section: Modelmentioning
confidence: 99%
“…The wave amplitude can be significantly amplified if these waves form a standing pattern inside the global magnetospheric resonator, formed by the entire magnetic flux tube [ Sato , 1978; Miura and Sato , 1980; Watanabe et al , 1993]. Numerical studies by Pokhotelov et al [2004] and Streltsov et al [2005] demonstrated that even a relatively weak (on the level of 10%) modification of the ionospheric conductivity by HF heaters can initiate IFI and enhance its development if the heating wave is modulated at the frequency of the most feedback‐unstable ULF mode. An experimental attempt to verify this theoretical prediction was made at the High Frequency Active Auroral Research Program (HAARP) facility on October 29, 2008 [ Streltsov et al , 2010a].…”
Section: Introductionmentioning
confidence: 99%
“…Trakhtengertz and Feldstein (984), and Lysak (1986Lysak ( , 1991 added models of such, in varying degrees of complexity. Numerical simulations of the instability development have been performed more recently (e.g., Lotko, 2003, 2004;Chaston et al, 2002;Pokhotelov et al, 2004). In the present work we examine the assumption, made in all previous works, that the ionosphere can be reasonably approximated by a thin layer -we find that it cannot.…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, precipitating electrons cause localized ionization and changes of ionospheric plasma conductivity (Demirkol et al 1999). The feedback of magnetospheric Alfvén waves and varying ionosphere conductivity lead to the creation of complex magnetosphere-ionosphere current systems (e.g., Pokhotelov et al 2004). Moreover, scattering of relativistic electrons by EMIC waves can also drive the X-ray bursts in the ionosphere (Lorentzen et al 2000;Millan et al 2002Millan et al , 2007.…”
Section: Effects Of Radiation-belt Electrons On the Ionospherementioning
confidence: 99%